2008
DOI: 10.1111/j.1651-2227.2007.00631.x
|View full text |Cite
|
Sign up to set email alerts
|

Standardized bench method for evaluating the efficacy of phototherapy devices

Abstract: We demonstrated the applicability of the method through the determination of the efficacy of several commercially available PT devices. This standardized method is reproducible and effectively evaluates the relative in vitro efficacy of various devices and may guide further in vitro and in vivo evaluations of devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 22 publications
1
43
0
Order By: Relevance
“…Therefore, it was recently suggested that a high hematocrit/hemoglobin level could reduce the therapeutic efficacy of phototherapy (26). In a post hoc analysis of hemoglobin data from our patients, we found a significant negative correlation between Hb and photoisomer formation during the early phase of phototerapy (15,30, and 60 min), which disappeared at the later time points. This fits with the fact that a difference only exists until an equilibrium between Z,E-and Z,Z-bilirubin is achieved.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Therefore, it was recently suggested that a high hematocrit/hemoglobin level could reduce the therapeutic efficacy of phototherapy (26). In a post hoc analysis of hemoglobin data from our patients, we found a significant negative correlation between Hb and photoisomer formation during the early phase of phototerapy (15,30, and 60 min), which disappeared at the later time points. This fits with the fact that a difference only exists until an equilibrium between Z,E-and Z,Z-bilirubin is achieved.…”
Section: Discussionmentioning
confidence: 69%
“…The efficacy of phototherapy depends on the irradiance and wavelength of the light, and on the irradiated skin area (3,14). The efficacy of phototherapy is also influenced by bedside optimization of spectral power (e.g., using reflecting surfaces), patient characteristics, and the phototherapy device characteristics (15). The 2004 American Academy of Pediatrics guidelines on management of neonatal jaundice defined intensive phototherapy as irradiance higher than 30 μW/cm 2 /nm over the 430-490 nm wavelength interval (16).…”
Section: Discussionmentioning
confidence: 99%
“…Emission spectra of various blue LEDs with peak wavelengths in the 400-500 nm range are nearly symmetric around their peaks with bandwidths of 25-30 nm (21,(41)(42)(43). The spectrum of the LEDs used here (460 nm peak and 28 nm bandwidth) was from that reported from a commercially available and widely used phototherapy system (41,42).…”
Section: Impact Of Quantity and Concentrationmentioning
confidence: 99%
“…The spectrum of the LEDs used here (460 nm peak and 28 nm bandwidth) was from that reported from a commercially available and widely used phototherapy system (41,42). The relative intensity at every 2 nm was incorporated into the database.…”
Section: Impact Of Quantity and Concentrationmentioning
confidence: 99%
“…Thus, it is becoming increasingly important that devices be evaluated for their physical and spectrophotometric characteristics as well as their clinical efficacy to affect the photochemical alteration of bilirubin (BR) in the newborn skin and circulation. The study reported by Subramanian, et al [4] in this issue of Indian Pediatrics significantly adds to the efforts that have already been made towards this goal [5][6][7], while it also demonstrates the diversity of traditional and new technologies.…”
Section: E D I T O R I a L E D I T O R I A L E D I T O R I A L E D I mentioning
confidence: 99%